Patrinia villosa (Thunb.) Juss alleviates CCL4-induced acute liver injury by restoring bile acid levels and inhibiting apoptosis/autophagy - Ye, Ji-Feng; Liu, Wei; Hou, Qishu; Bai, Shu-Qi; Xiang, Zheng; Wang, Jiaqi; Qiao, Liman (Frontiers in Pharmacology, 2024)
Background: Patrinia Villosa (Thunb.) Juss is one of the plant resources of the famous traditional Chinese medicine "Baijiangcao (herba patriniae)", and is considered to function at liver meridian thereby treating diseases of the liver as demonstrated by the traditional theory of TCM. Unfortunately, the therapeutic mechanism of the whole plant of PV is so far unknown.Method: UPLC QTOF-MS/MS was used to analyze the profile of the PV. Male Sprague-Dawley rats were divided into five groups, PV groups (125 and 375 mg/kg) were administered by oral gavage for 7 consecutive days. The model of liver injury was induced by intraperitoneal injection of 40% CCl4 oil solution. H&E staining was used for histological evaluation. ELISA method was used to assess the serum level of ALT, AST, and T-BIL. Serum and liver bile acids (BAs) profiling were analyzed by LC-MS/MS. TUNEL-stained liver sections were used to monitor apoptosis caused by CCl4. HepG2 cells were used to detect autophagy caused by CCl4.Results: 16 compounds were identified from the 70% methanol extract of PV. PV. (125 and 375 mg/kg) could reverse the ectopic overexpression of AST, ALT, and T-BIL caused by CCl4 administration. H&E staining indicated the PV (125 and 375 mg/kg) could reduce the infiltration of inflammatory cells, and restore liver tissue and hepatocyte structures. 6 bile acids, including DCA, HDCA, GCA, TCA, TCDCA, and TUDCA, were significantly altered both in serum and liver tissue after CCl administration and the level of all these 6 bile acids was restored by PV treatment. Moreover, PV inhibited apoptosis caused by CCl4 stimulation in liver tissue and suppressed autophagy in HepG2 cells treated with CCl4.The results in this paper for the first time reveal the alteration of bile acid profile in CCl4induced liver injury and demonstrate that inhibiting apoptosis and autophagy was involved in P. villosa-elicited liver protection, providing a scientific basis for the clinical utilization of P. villosa as natural hepatic protective agents.